"This disease has made me lose the belief I had in myself": qualitative analysis of experiences among buruli ulcer disease patients in Nigeria using the socioecological model of health - Precious Chidozie Azubuike; Ebuka Light Onyekachi; Michael Obule Enyam; Miracle Nwadiche; Chimankpam Kingsley Ogbonna; Promise Nmesomachi Timothy; Eberechukwu Ruth Uchegbu; James Abuo; Temidayo Akinreni (Discover Public Health)
Abstract Introduction Buruli Ulcer Disease is a debilitating neglected tropical disease caused by “Mycobacterium ulcerans”, predominantly affecting marginalized populations in tropical and subtropical regions, including Nigeria. Previous studies have reported a prevalence rate of 61.3% for the disease, highlighting its significant burden on affected communities. Much of the existing research has focused on the biomedical aspects of BUD, often neglecting the sociocultural and environmental dimensions crucial to patient experiences and outcomes. This study utilizes the socioecological model of health to explore the complex interplay of individual, interpersonal, community, and societal factors shaping the experiences of buruli ulcer disease patients in Nigeria. Methods Our qualitative study was conducted among people living with buruli ulcer disease in Enugu state. Data collection involved only one Focus Group Discussion with eight discussants due to the sensitive nature of the topic, and six Key Informant Interviews, encompassing a diverse group of buruli ulcer disease patients. The WHO Quality of Life-BREF was adapted for data collection, which was conducted by a trained team. Data were analyzed using content analysis to inductively code themes and identify overarching categories, supported by NVivo (version 12). Results Our findings reveal the diverse experiences of patients across various levels of socioecological model. At the individual level: participants reported significant physical and psychological challenges, including persistent pain, discomfort, disfigurement, and the emotional toll of stigmatization. Interpersonal level: experiences of social rejection, loss of social roles, and abandonment by family members were reported. These interpersonal challenges were exacerbated by the stigma surrounding the disease, leading to strained relationships and a sense of isolation within their social circles. At the organizational level: some individuals experienced compassion and assistance, others faced social isolation, discrimination, and exclusion due to misconceptions. Broader community level included limited awareness, which resulted in a lack of resources and formal support systems. Conclusion BUD patients in Nigeria endure considerable negative psychosocial experiences, particularly at the interpersonal and community levels. Enhancing community awareness and support is crucial to mitigating these impacts. Further research should explore family-level psychosocial experiences and other contributing factors to provide a more comprehensive understanding and inform effective intervention strategies.